A gas diffusion layer with good water management performance and preparation method thereof

By designing the hydrophilic micro -pores distributed by the base layer and micropore layer of the gas diffusion layer, the problem of poor water management of the existing technology is solved, and the drainage and low humidity are achieved under high humidity drainage and low humidity under high humidity. The good water management performance of water preservation has improved the power generation performance of fuel cells.

CN119108565BActive Publication Date: 2025-01-28CAS LINKFIBER NEW MATERIALS (CHANGZHOU) CO LTD

Patent Information

Application Number
CN202411585612.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing gas diffusion layer is difficult to effectively manage moisture under high humidity and low humidity conditions, resulting in flooding or drying of the membrane, affecting the power generation performance of the fuel cell.

Method used

The gas diffusion layer with the base layer with hydrophilic micro -channel and the microporous layer is used. The base layer runs through several hydrophilic micro -channels. The microre layer is distributed with double -peak pores, including micron levels and nano -level pores. The filtration speed adjustment forms an orderly hydrophilic micro -channel.

Benefits of technology

Drainage under high humidity to avoid flooding; keep water under low humidity, avoid the problem of low proton transmission efficiency caused by dried membranes, and improve the water management performance of fuel cells and the stability of the battery gas supply.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119108565B_ABST
    Figure CN119108565B_ABST
Patent Text Reader

Abstract

The invention relates to the field of fuel cells, and in particular to a gas diffusion layer with good water management performance and a preparation method thereof; the gas diffusion layer comprises: a substrate layer and a microporous layer; the substrate layer comprises: a plurality of hydrophilic microchannels penetrating the substrate layer; the invention is based on the difference in response of hydrophilic polymers and polytetrafluoroethylene to shear rate in an aqueous solution system, and forms ordered hydrophilic microchannels inside carbon paper by adjusting the suction filtration speed; under high humidity conditions, the hydrophilic microchannels are conducive to the introduction of liquid water into the carbon paper and rapid discharge, and can solve the problem of water flooding at the interface between the carbon paper and the microporous layer and inside the carbon paper that cannot be solved by the prior art, and at the same time, the hydrophobicity of the local area is enhanced to form a water-free area, which is conducive to the introduction of reaction gas; under low humidity conditions, the hydrophilic polymers of the hydrophilic microchannels are more likely to combine with water to maintain a wet state, and can be used as a water storage layer to maintain membrane wetness to achieve self-humidification, thereby improving the low-humidity performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a gas diffusion layer with good water management performance and a preparation method thereof. Background Art

[0002] Proton Exchange Membrane Fuel Cell (PEMFC) is a power generation device that uses the redox reaction of hydrogen and oxygen to directly convert chemical energy into electrical energy. It is currently a very competitive energy utilization device.

[0003] The gas diffusion layer (GDL) is a key material that affects the power generation performance of PEMFC. It is responsible for supporting the catalyst layer, collecting current, transmitting gas and managing water. As a multiphase transmission channel for gas and water, the mass transfer efficiency of GDL directly affects the power generation performance of the fuel cell. When the battery is operated under high humidity and high current density conditions, a large amount of liquid water will be generated. If it cannot be removed in an orderly and timely manner, it will cause "flooding", which will hinder the introduction of the reaction gas in the diffusion layer, thereby affecting the power generation performance of the fuel cell; under low humidity and low current density conditions, the water content inside the battery is low, and the membrane proton conductivity is prone to low, which in turn affects the battery performance. With the expansion of fuel cell application scenarios, higher requirements are put forward for the gas diffusion layer to have both good drainage and water retention properties.

[0004] GDL is usually composed of a macroporous substrate layer and a microporous layer (MPL). In the current general technology of gas diffusion layer, the substrate is a hydrophobic macroporous carbon paper. In order to improve the water management performance of the diffusion layer, the MPL is often selected for structural design. Patent CN104541395A proposes that hydrophilic additives such as tin oxide and titanium dioxide are added to the microporous layer, which can effectively reduce the flooding of water in the catalyst layer. However, the conductivity of the oxide is poor, which will cause the battery impedance to increase, thereby reducing the battery performance. In the prior art, there are also U.S. patents such as US8945790 and Chinese patents CN103956505A, which provide a method of improving the water management performance of a gas diffusion layer with a gradient structure by compounding multiple microporous layers. However, the substrate layers are all micron-sized pores, and the capillary force is weaker, which is more unfavorable for water removal. Water is still prone to accumulation in the hydrophobic substrate layer or at the interface between the substrate layer and the MPL. The design of the microporous layer can only reduce the flooding phenomenon in the MPL and the catalyst layer, and cannot completely solve the problem of GDL flooding. Summary of the invention

[0005] The object of the present invention is to provide a gas diffusion layer with good water management performance and a preparation method thereof in view of the deficiencies in the prior art.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention is to provide a gas diffusion layer with good water management performance, comprising: a base layer and a microporous layer arranged on the top of the base layer; the base layer comprises: a plurality of hydrophilic microchannels penetrating the base layer; the microporous layer has a plurality of micropores, and the pore size distribution of the micropores includes two most probable pore sizes.

[0008] Preferably, the thickness ratio of the base layer to the microporous layer is (3-8):1.

[0009] Preferably, in the base layer, the ratio of the hydrophilic microchannel to the hydrophobic region is 1:(50-150).

[0010] Preferably, the two most probable pore sizes are the micrometer-scale most probable pore size and the nanometer-scale most probable pore size; the pore size of the micrometer-scale micropores is 1 μm-10 μm, and the pore size of the nanometer-scale micropores is 20 nm-400 nm; in the microporous layer, the volume ratio of the micrometer-scale micropores to the nanometer-scale micropores is (0.4-0.8):1.

[0011] The second aspect of the present invention is to provide a method for preparing the above-mentioned gas diffusion layer, the steps comprising:

[0012] S1. Weigh polytetrafluoroethylene, a dispersant and a hydrophilic polymer, dissolve them in water and stir to prepare a first slurry;

[0013] S2, fixing the carbon paper on the suction filtration device, and adding the first slurry into the suction filtration device for suction filtration treatment to achieve hydrophobic treatment of the carbon paper; drying the hydrophobic treated carbon paper to obtain a base layer;

[0014] S3, weighing a dispersant and carbon powder, mixing them with water, and then ball milling and sand milling to obtain a conductive slurry;

[0015] S4, mixing the conductive paste with polytetrafluoroethylene, the first pore-forming agent and the second pore-forming agent, coating the mixture on the surface of the base layer, and sequentially performing drying and sintering treatments to obtain a gas diffusion layer.

[0016] Preferably, in step S1, the concentration of polytetrafluoroethylene is 5wt%-10wt%;

[0017] The dispersant includes: at least one of Triton, polyoxyethylene ether, Span, and Span; the amount of the dispersant is 20%-80% of the polytetrafluoroethylene;

[0018] The hydrophilic polymer includes at least one of polyvinyl alcohol, polyvinyl pyrrolidone, epoxy resin, polyacrylamide and polyethylene oxide; the amount of the hydrophilic polymer is 0.005%-0.5% of polytetrafluoroethylene.

[0019] Preferably, in step S2, the filtration treatment comprises: firstly 2 .s)-500mL / (cm 2 .s) for rapid filtration, and then at 20mL / (cm 2 .s)-50mL / (cm 2 .s) for slow filtration; the time ratio of fast filtration to slow filtration is 1:(0.2-1).

[0020] Preferably, in step S3, the carbon powder includes at least one of acetylene black, carbon nanotubes, Ketjen black, nano-carbon fibers, and graphite powder.

[0021] More preferably, when there are two or more types of carbon powder, one of them is main carbon powder, and the amount of the main carbon powder is 50%-90% of the total carbon powder mass.

[0022] Preferably, in step S4, the first pore-forming agent includes: ammonium chloride, ammonium bicarbonate, ammonium sulfate, sodium carbonate-type inorganic salts; the second pore-forming agent includes: polyethylene oxide, polypropylene oxide, polyethylene glycol, polyvinyl alcohol, polyacrylamide-type polymer materials; the weight ratio of the first pore-forming agent to the second pore-forming agent is 1:(0.1-0.6).

[0023] More preferably, the total amount of the first pore-forming agent and the second pore-forming agent is 0.5%-5% of the amount of the carbon powder.

[0024] Preferably, in step S4, the sintering temperature is 350° C.-380° C., and the sintering time is 20 min-80 min.

[0025] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:

[0026] (1) The bimodal pore size distribution of the microporous layer can achieve water drainage under high humidity to avoid water flooding in the catalyst layer and the microporous layer, and can retain water under low humidity to avoid the problem of low proton transfer efficiency caused by membrane drying. The present invention achieves a balance between water drainage and water retention by controlling the ratio of micron-sized pores and nano-sized pores in the bimodal pore size distribution, and can achieve good water management performance of water drainage under high humidity and water retention under low humidity.

[0027] (2) In the present invention, the base layer has hydrophobic properties and also has hydrophilic microchannels, which is beneficial to efficient drainage under high humidity and water retention under low humidity. Based on the difference in the response of hydrophilic polymers and polytetrafluoroethylene to shear rate in an aqueous solution system, the present invention forms ordered hydrophilic microchannels inside the carbon paper by adjusting the filtration speed. Under high humidity conditions, the hydrophilic microchannels are beneficial to the introduction of liquid water into the carbon paper and its rapid discharge, which can solve the problem of water flooding at the interface between the carbon paper and the microporous layer and inside the carbon paper that cannot be solved by the prior art. At the same time, the hydrophobicity of the local area is enhanced to form a water-free area, which is beneficial to the introduction of the reaction gas. Under low humidity conditions, the hydrophilic polymers in the hydrophilic microchannels are more likely to combine with water and maintain a wet state, and can be used as a water storage layer to maintain the membrane wetness to achieve self-humidification, thereby improving the low-humidity performance of the battery.

[0028] (3) The distribution setting of hydrophilic microchannels can effectively shorten the mass transfer path, further improve the mass transfer efficiency, and improve the gas supply stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the structure of the gas diffusion layer of the comparative example;

[0030] Figure 2 Schematic diagram of the structure of the gas diffusion layer of the present invention.

[0031] Reference numerals in the figures include:

[0032] Base layer 1; hydrophilic microchannel 11; microporous layer 2. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0035] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0036] Example 1

[0037] This embodiment provides a gas diffusion layer and a method for preparing the same. The preparation steps include:

[0038] S1, mixing and stirring a 5wt% polytetrafluoroethylene aqueous solution (PTFE), Triton (20% of PTFE) and a hydrophilic polymer (polyvinyl alcohol: polyvinyl pyrrolidone = 1:1) to prepare a first slurry; the amount of the hydrophilic polymer is 0.005% of PTFE;

[0039] S2, the carbon paper was washed with ethanol and water and then dried at 80℃ for 30min. The treated carbon paper was fixed on the suction filtration device, and the first slurry was added to the suction filtration device. The suction filtration speed was controlled at 100mL / (cm 2 .s) Filter for 5 minutes, then adjust the filtration speed to 20mL / (cm 2 .s) After filtration for 1 minute, drying at 80°C for 30 minutes, a base layer 1 having hydrophilic microchannels 11 is obtained; the ratio of the hydrophilic microchannels to the hydrophobic regions is 1:50;

[0040] S3, mixing water, dispersant, acetylene black and carbon nanotubes in a weight ratio of 100:0.5:9:1, first ball milling for 0.5 h, and then sand milling for 0.5 h to obtain a conductive slurry;

[0041] S4. Mix the conductive slurry with PTFE, ammonium chloride and polyethylene glycol in a weight ratio of 100:5:0.0450:0.0045, and use double planetary stirring for 0.5h to obtain a coating slurry; fix the base layer 1 on the coating panel, and use a doctor blade coating process to coat the coating slurry on one side of the base layer 1, dry it at 80°C for 30min, and sinter it at 350°C for 80min to obtain a gas diffusion layer.

[0042] The thickness of the base layer 1 of the gas diffusion layer is 190 μm, the thickness of the microporous layer 2 is 30 μm, and the volume ratio of the micropores of micrometer scale to the micropores of nanometer scale in the microporous layer 2 is 0.4:1.

[0043] Example 2

[0044] This embodiment provides another gas diffusion layer and a preparation method thereof, the preparation steps comprising:

[0045] S1, mixing and stirring a 10wt% polytetrafluoroethylene aqueous solution (PTFE), polyoxyethylene ether (the amount used is 80% of PTFE) and a hydrophilic polymer (polyacrylamide:polyoxyethylene=1:0.5) to prepare a first slurry; the amount of the hydrophilic polymer is 0.5% of PTFE;

[0046] S2, the carbon paper was washed with ethanol and water and dried at 80℃ for 40min, the treated carbon paper was fixed on the suction filtration device, and the first slurry was added to the suction filtration device, and the suction filtration speed was controlled at 500mL / (cm 2 .s) Filter for 2 minutes, then adjust the filtration speed to 50mL / (cm2 .s) After filtration for 2 minutes, drying at 80°C for 30 minutes, a base layer 1 having a hydrophilic microchannel 11 is obtained; the ratio of the hydrophilic microchannel to the hydrophobic region is 1:150;

[0047] S3, mixing water, dispersant and Ketjen black in a weight ratio of 100:0.2:10, first ball milling for 0.5 h, and then sand milling for 0.5 h to prepare a conductive slurry;

[0048] S4. Mix the conductive slurry with PTFE, ammonium chloride and polyethylene glycol in a weight ratio of 100:2:0.3125:0.1875, and use double planetary stirring for 1 hour to obtain a coating slurry; fix the base layer 1 on the coating panel, and use a doctor blade coating process to coat the coating slurry on one side of the base layer 1, dry it at 80°C for 30 minutes, and sinter it at 380°C for 20 minutes to obtain a gas diffusion layer.

[0049] The thickness of the base layer 1 of the gas diffusion layer is 150 μm, the thickness of the microporous layer 2 is 50 μm, and the volume ratio of the micropores of micrometer scale to the nanopores of nanometer scale in the microporous layer 2 is 0.8:1.

[0050] Example 3

[0051] This embodiment provides another gas diffusion layer and a preparation method thereof, the preparation steps comprising:

[0052] S1, mixing and stirring 8 wt % polytetrafluoroethylene aqueous solution (PTFE), Span (in an amount of 20% of PTFE) and epoxy resin (in an amount of 0.01% of PTFE) to prepare a first slurry;

[0053] S2, the carbon paper was washed with ethanol and water and then dried at 80℃ for 60min. The treated carbon paper was fixed on the suction filtration device, and the first slurry was added to the suction filtration device. The suction filtration speed was controlled at 200mL / (cm 2 .s) Filter for 3 minutes, then adjust the filtration speed to 40mL / (cm 2 .s) After filtration for 1.5 minutes, drying at 80°C for 30 minutes, a base layer 1 having hydrophilic microchannels 11 is obtained; the ratio of the hydrophilic microchannels to the hydrophobic regions is 1:110;

[0054] S3, mixing water, dispersant, acetylene black and graphite powder in a weight ratio of 100:0.1:6:6, first ball milling for 0.5 h, then sand milling for 0.5 h to obtain a conductive slurry;

[0055] S4. Mix the conductive slurry with PTFE, ammonium chloride and polyethylene glycol in a weight ratio of 100:8:0.5:0.1, and use double planetary stirring for 0.5h to obtain a coating slurry; fix the base layer 1 on the coating panel, and use a doctor blade coating process to coat the coating slurry on one side of the base layer 1, dry it at 80°C for 30min, and sinter it at 360°C for 50min to obtain a gas diffusion layer.

[0056] The thickness of the base layer 1 of the gas diffusion layer is 240 μm, the thickness of the microporous layer 2 is 30 μm, and the volume ratio of the micropores of micrometer scale to the nanopores of nanometer scale in the microporous layer 2 is 0.7:1.

[0057] Comparative Example

[0058] This comparative example provides a gas diffusion layer, comprising: a base layer and a microporous layer; the base layer is carbon paper with a hydrophobic surface, and the microporous layer has a nanometer-level most probable pore size.

[0059] Detection Example

[0060] The performance of the batteries made of the gas diffusion layers of Examples 1-3 and the comparative example was tested respectively, and the test results are shown in Table 1;

[0061] Table 1

[0062]

[0063] The bimodal pore size distribution of the microporous layer of the present invention can achieve drainage under high humidity to avoid water flooding in the catalyst layer and the microporous layer, and can retain water under low humidity to avoid the problem of low proton transfer efficiency caused by membrane drying. According to the Young-Laplace equation, as the pore size decreases, the capillary pressure increases accordingly. Under high humidity conditions, the abundant small pores in the microporous layer (nanoscale most probable pore size distribution) will provide a greater capillary force, overcoming the hydrophobic force to guide water out of the catalyst layer and into the GDL, avoiding water accumulation in the catalyst layer and causing flooding; at this time, the capillary force of the larger pores (micrometer-scale most probable pore size distribution) is not enough to overcome the hydrophobic force, which can retain the mass transfer channel for the reaction gas transmission; under low humidity conditions, the water pressure of the catalyst layer decreases, and the drainage capacity of the smaller pores in the microporous layer is weakened. The hydrophobic force prevails in both the micrometer-scale and nanometer-scale pore structures. At this time, the hydrophobic properties of the microporous layer can The water is pushed to the catalyst layer and then wets the proton membrane, alleviating the problem of difficulty in proton transport caused by over-drying of the membrane. In the prior art, hydrophilic substances are often added to the microporous layer to impart water-retaining properties. Such a solution will improve the low-humidity performance, but the presence of hydrophilic substances will lock excess water in the microporous layer under conditions of high moisture content, which may easily cause the microporous layer to be flooded under high humidity or high current density. The present invention achieves a balance between drainage and water retention by controlling the ratio of micron-sized pores and nano-sized pores in the bimodal pore size distribution, thereby achieving good water management performance of drainage under high humidity and water retention under low humidity.

[0064] The hydrophilic microchannels and hydrophobic properties in the carbon paper of the present invention are conducive to efficient drainage under high humidity and water retention under low humidity. High shear rate is conducive to the straightening and expansion of hydrophilic polymer chains but will cause PTFE microcrystallization, and low shear rate is conducive to uniform distribution of PTFE, but low shear rate for too long will cause the hydrophilic polymer chains to curl.

[0065] In the present invention, based on the difference in the response of the hydrophilic polymer chain and the PTFE molecular chain to the shear rate in the aqueous solution system, the orderly hydrophilic microchannels are formed inside the carbon paper by adjusting the filtration speed. A higher filtration speed can provide a greater shear rate, which is beneficial to straighten the curled hydrophilic polymer chain and facilitate its vertical distribution in the shortest path in the carbon paper. When the filtration speed is greater than 500mL / (cm 2 .s), too large a shear rate may cut the hydrophilic polymer chain and cause discontinuity in the transmission path. When the filtration rate is less than 100mL / (cm 2 .s), the shear rate is not enough to straighten the polymer chain, and the bending state is prone to form water accumulation areas or lengthen the transmission path. A lower filtration speed is conducive to the uniform distribution of the hydrophobic agent PTFE in the gap of the hydrophilic channel, ensuring a stable and uniform supply of the reaction gas, and the speed is higher than 50mL / (cm 2 .s), which is not conducive to adequate distribution, and the speed is lower than 20mL / (cm 2.s) The distributed hydrophilic polymers may curl up, which is not conducive to the stability of the hydrophilic channel. The time ratio control of the two is also the key to process control. If the fast filtration time ratio is too long, the PTFE will be oriented under long-term high-speed shearing, resulting in uneven hydrophobic distribution. If the slow filtration time ratio is too long, the hydrophilic molecular chain will curl up.

[0066] Under high humidity conditions, the hydrophilic microchannels are conducive to the introduction of liquid water into the carbon paper and its rapid discharge, which can solve the problem of water flooding at the interface between the carbon paper and the microporous layer and inside the carbon paper that cannot be solved by existing technologies. At the same time, the hydrophobicity of local areas is enhanced to form water-free areas, which is conducive to the introduction of reaction gases. Under low humidity conditions, the hydrophilic polymers of the hydrophilic microchannels are easier to combine with water to maintain a wet state, and can be used as a water storage layer to maintain the membrane moist to achieve self-humidification, thereby improving the low-humidity performance of the battery.

[0067] The present invention can effectively shorten the mass transfer path through the distribution of hydrophilic channels, further improve the mass transfer efficiency, and improve the gas supply stability of the battery.

[0068] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a gas diffusion layer with good water management performance, characterized in that the steps include: S1. Weigh polytetrafluoroethylene, a dispersant and a hydrophilic polymer, dissolve them in water and stir to prepare a first slurry; S2, fixing the carbon paper on the suction filtration device, and adding the first slurry into the suction filtration device for suction filtration treatment to achieve hydrophobic treatment of the carbon paper; The carbon paper after the hydrophobic treatment is dried to obtain the base layer (1); the filtration treatment includes: firstly filtration at 100 mL / (cm 2 .s)-500mL / (cm 2 .s) for rapid filtration, and then at 20mL / (cm 2 .s)-50mL / (cm 2 .s) for slow filtration; the time ratio of fast filtration to slow filtration is 1:(0.2-1); S3, weighing a dispersant and carbon powder, mixing them with water, and then ball milling and sand milling to obtain a conductive slurry; S4, mixing the conductive paste with polytetrafluoroethylene, the first pore-forming agent and the second pore-forming agent, coating the mixture on the surface of the base layer (1), and performing drying and sintering treatments in sequence to obtain a gas diffusion layer.

2. The preparation method according to claim 1, characterized in that: In step S1, the concentration of polytetrafluoroethylene is 5wt%-10wt%; The dispersant includes: at least one of Triton, polyoxyethylene ether, Span, and Span; the amount of the dispersant is 20%-80% of the polytetrafluoroethylene; The hydrophilic polymer includes at least one of polyvinyl alcohol, polyvinyl pyrrolidone, epoxy resin, polyacrylamide and polyethylene oxide; the amount of the hydrophilic polymer is 0.005%-0.5% of polytetrafluoroethylene.

3. The preparation method according to claim 1, characterized in that: In step S3, the carbon powder includes at least one of acetylene black, carbon nanotubes, Ketjen black, nano-carbon fibers, and graphite powder.

4. The preparation method according to claim 1, characterized in that: In step S4, the first pore-forming agent includes: ammonium chloride, ammonium bicarbonate, ammonium sulfate, sodium carbonate-type inorganic salts; the second pore-forming agent includes: polyethylene oxide, polypropylene oxide, polyethylene glycol, polyvinyl alcohol, polyacrylamide-type polymer materials; the weight ratio of the first pore-forming agent to the second pore-forming agent is 1: (0.1-0.6).

5. The preparation method according to claim 1, characterized in that: In step S4, the sintering temperature is 350° C.-380° C., and the sintering time is 20 min-80 min.

6. A gas diffusion layer with good water management performance prepared by the preparation method according to any one of claims 1 to 5, characterized in that: include: A base layer (1) and a microporous layer (2) arranged on the top of the base layer (1); the base layer (1) comprises: a plurality of hydrophilic microchannels (11) penetrating the base layer (1); the microporous layer (2) has a plurality of micropores, and the pore size distribution of the micropores includes two most probable pore sizes.

7. The gas diffusion layer according to claim 6, characterized in that: The thickness ratio of the base layer (1) to the microporous layer (2) is (3-8):

1.

8. The gas diffusion layer according to claim 6, characterized in that: In the base layer (1), the ratio of the hydrophilic microchannel (11) to the hydrophobic region is 1:(50-150).

9. The gas diffusion layer according to claim 6, characterized in that: The two most probable pore sizes are a micrometer-scale most probable pore size and a nanometer-scale most probable pore size; the pore size of the micrometer-scale micropores is 1 μm-10 μm, and the pore size of the nanometer-scale micropores is 20 nm-400 nm; in the microporous layer (2), the volume ratio of the micrometer-scale micropores to the nanometer-scale micropores is (0.4-0.8):1.

Citation Information

Patent Citations

  • Gas diffusion layer with water retaining property for fuel cell, preparation method of gas diffusion layer, membrane electrode assembly and application

    CN103956505A

  • Microporous layer with hydrophilic additives

    CN104541395A

  • Microporous layer structures and gas diffusion layer assemblies in proton exchange membrane fuel cells

    US8945790B2

  • Integrated reversible fuel cell membrane electrode cathode side structure

    CN113140768A

  • Self-humidifying water-retaining gas diffusion layer and preparation method thereof

    CN116632272A

Cited By

  • Hydrophilic gas diffusion layer and preparation method thereof

    CN122214903A